2013
DOI: 10.1186/1746-6148-9-19
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory capacity for diagnosis of foot-and-mouth disease in Eastern Africa: implications for the progressive control pathway

Abstract: BackgroundAccurate diagnosis is pertinent to any disease control programme. If Eastern Africa is to work towards control of foot-and-mouth disease (FMD) using the Progressive Control Pathway for FMD (PCP-FMD) as a tool, then the capacity of national reference laboratories (NRLs) mandated to diagnose FMD should match this task. This study assessed the laboratory capacity of 14 NRLs of the Eastern Africa Region Laboratory Network member countries using a semi-structured questionnaire and retrospective data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Although the provision of simple FMDV‐positive/negative results is sufficient for the confirmation of FMD during outbreaks, the value of this information is limited in countries where FMD is endemic. In these situations, it is beneficial to characterize circulating FMDV outbreaks in order to make tailored control programmes a realistic possibility (Namatovu et al., ). In support of this, this study also evaluated a lyophilized version of a published FMDV‐typing assay specific to East Africa (Bachanek‐Bankowska et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the provision of simple FMDV‐positive/negative results is sufficient for the confirmation of FMD during outbreaks, the value of this information is limited in countries where FMD is endemic. In these situations, it is beneficial to characterize circulating FMDV outbreaks in order to make tailored control programmes a realistic possibility (Namatovu et al., ). In support of this, this study also evaluated a lyophilized version of a published FMDV‐typing assay specific to East Africa (Bachanek‐Bankowska et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from serotype O, other serotypes including A, SAT 1 and SAT 2 have also been recently in circulation (Namatovu et al, 2013), while previously, serotype C has also been identified within the region (Vosloo et al, 2002). However, serotype C was last isolated from Kenyan cattle in 2004 (Roeder and Knowles, 2009;Sangula et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A clear global picture of the distribution and movements of FMD strains within and between regions and countries is lacking. This is partly due to limited diagnostic capacity and limited sampling in many endemic countries (Namatovu et al., ). Cost, complexity and biosafety requirements of current tests (antibody and antigen) present a barrier to some countries wishing to perform more FMD diagnostics.…”
Section: Introductionmentioning
confidence: 99%